Exploring Chinese students' strategy use in a cooperative peer feedback writing group. (June 2016) - Yu, Shulin; Lee, Icy
Abstract: While research on peer feedback has proliferated over the past two decades, little attention has been paid to the strategies L2 learners employ while they are engaged in peer feedback activities in the L2 writing classroom. To fill such a void in the research literature, this case study explores the peer feedback strategies adopted by four Chinese EFL learners from an Activity Theory perspective. Multiple sources of data were collected, including video recordings of peer feedback sessions, semi-structured interviews, stimulated recalls, and student drafts of writing. The study reveals that this group of engaged and collaborative EFL students adopted five major strategies in peer feedback: Using L1 (Mandarin Chinese) (Artefact), employing L2 writing criteria (Rule), adopting rules of group activity (Rule), seeking help from teachers (Community), and playing different roles (Division of labor). The findings show that students as agents of the activity employ these strategies to facilitate their group interaction. The reconceptualization of peer feedback from the Activity Theory perspective highlights that peer feedback is a socially mediated activity in which students use strategies to facilitate their group interaction.